2019
DOI: 10.1016/j.ejvssr.2018.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Acute Leg Ischaemia in a Child due to a Thrombosed Popliteal Aneurysm

Abstract: IntroductionThe case of an idiopathic thrombosed popliteal aneurysm is described in an otherwise healthy 6 year old child. This is the fourth reported case and the second youngest patient to present with an idiopathic isolated popliteal aneurysm.ReportA 6 year old boy presented with an acutely ischaemic right foot. Computed tomography angiography confirmed a thrombosed popliteal aneurysm. A femoropopliteal bypass was performed with reversed long saphenous vein and ligation of the aneurysm. Yearly follow up is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Aneurysms may manifest as asymptomatic or present as a pulsatile mass with shivering, local pain and ischemic pain 10 . In this case, the patient presented with venous congestion, visible superficial venous system and edema with increased circumference of the right lower limb with respect to the contralateral limb, clinical signs that had not been reported in the cases previously described so far in the literature 3,4,8,12,13 . Diagnosis is made by clinical examination and complementary tests such as echo-Doppler, angiography, computed axial tomography or magnetic resonance angiography.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…Aneurysms may manifest as asymptomatic or present as a pulsatile mass with shivering, local pain and ischemic pain 10 . In this case, the patient presented with venous congestion, visible superficial venous system and edema with increased circumference of the right lower limb with respect to the contralateral limb, clinical signs that had not been reported in the cases previously described so far in the literature 3,4,8,12,13 . Diagnosis is made by clinical examination and complementary tests such as echo-Doppler, angiography, computed axial tomography or magnetic resonance angiography.…”
Section: Discussionmentioning
confidence: 67%
“…In the cases reported in the literature, aneurysm resection is performed 3,4,12,13 . However, in the present case, it was decided not to perform such resection and it was managed with proximal and distal ligation, following the conduct taken in other cases reported in the literature 8 , seeking to obtain a shorter surgical time, less risk of injury to surrounding structures, and avoiding the need to release muscle bundles.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…There have been no strictly randomized controlled studies exploring the best surgical treatment for this disease. The present studies on thrombotic PAA with ALI were mainly case reports with heterogeneous results [25,30]. Marko Dragas et al [6] reported a group of 156 patients with acute thrombotic PAA and suggested that intraoperative thrombolysis can improve the long-term patency rate and reduce the incidence of complications.…”
Section: Discussionmentioning
confidence: 88%